2023
DOI: 10.1039/d2qi02482a
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of Mg carbonates precipitation and implications for CO2 capture and utilization/storage

Abstract: The mechanisms involved in the natural formations of dolomite (CaMg(CO3)2) and magnesite (MgCO3) have endured as challenging research questions over centuries, being yet a matter under investigation in multiple fields....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 163 publications
(451 reference statements)
0
7
0
Order By: Relevance
“…Under ambient conditions, however, recent work demonstrated that hydrated Mg carbonate phases form, which significantly change the efficiency and, hence, the economics of the proposed looping process. The formation of hydrous magnesium carbonates depends upon multiple variables, and it is not obvious which chemical pathway will be preferable under ambient environmental conditions . Previous work on Mg­(OH) 2 or forsterite carbonation and evidence from weathering studies show that mineral reactions in both laboratory and field environments can be slowed down by the formation of a passivation layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under ambient conditions, however, recent work demonstrated that hydrated Mg carbonate phases form, which significantly change the efficiency and, hence, the economics of the proposed looping process. The formation of hydrous magnesium carbonates depends upon multiple variables, and it is not obvious which chemical pathway will be preferable under ambient environmental conditions . Previous work on Mg­(OH) 2 or forsterite carbonation and evidence from weathering studies show that mineral reactions in both laboratory and field environments can be slowed down by the formation of a passivation layer.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of hydrous magnesium carbonates depends upon multiple variables, and it is not obvious which chemical pathway will be preferable under ambient environmental conditions. 7 Previous work on Mg(OH) 2 8 or forsterite 9 11 carbonation and evidence from weathering studies 12 14 show that mineral reactions in both laboratory and field environments can be slowed down by the formation of a passivation layer. While the formation of hydrated Mg carbonate phases was previously observed, 6 it was not assessed whether these passivate the reactive surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Those minerals in general show a larger carbon storage potential compared to their industrial counterparts and are described to be applied for enhanced carbonation measures. The values for this category are obtained from various review papers [14,16,[26][27][28]31,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…The technological pathways pursued for CO 2 capture include precombustion (CO 2 concentration of 15–60% and partial pressure of 2–7 MPa), postcombustion (CO 2 concentration of 3–20% and partial pressure of 0.003–0.02 MPa), oxy-fuel combustion routes (CO 2 concentration > 95% and partial pressure of 0.1–0.5 MPa), and direct air carbon capture (CO 2 concentration of ∼400 ppm and pressure < 0.1 MPa) . The existing CO 2 capture techniques include, absorption, adsorption, membrane separation, cryogenic separation, mineral carbonation, bioenergy with carbon capture and storage (BECCS), and direct air capture (DAC) . Among all these methods, solvent-based absorption is the most widely used, due to its high efficiency and low cost of operation .…”
Section: Introductionmentioning
confidence: 99%